2015
DOI: 10.1377/hlthaff.2014.0945
|View full text |Cite
|
Sign up to set email alerts
|

A Public-Private Partnership Improves Clinical Performance In A Hospital Network In Lesotho

Abstract: Health care public-private partnerships (PPPs) between a government and the private sector are based on a business model that aims to leverage private-sector expertise to improve clinical performance in hospitals and other health facilities. Although the financial implications of such partnerships have been analyzed, few studies have examined the partnerships' impact on clinical performance outcomes. Using quantitative measures that reflected capacity, utilization, clinical quality, and patient outcomes, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 16 publications
2
58
1
6
Order By: Relevance
“…Key informants identified major improvements in the new hospital network compared to the government-managed facilities it replaced and related those changes to staff motivation and patient care outcomes. The qualitative data largely support the quantitative findings, previously reported, 17 which showed significant improvements in clinical outcomes. Some differences noted by informants, such as new clinical services and better infrastructure, are to be expected with any new facility, and such investments could also have been introduced in a publicly run hospital.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Key informants identified major improvements in the new hospital network compared to the government-managed facilities it replaced and related those changes to staff motivation and patient care outcomes. The qualitative data largely support the quantitative findings, previously reported, 17 which showed significant improvements in clinical outcomes. Some differences noted by informants, such as new clinical services and better infrastructure, are to be expected with any new facility, and such investments could also have been introduced in a publicly run hospital.…”
Section: Discussionsupporting
confidence: 88%
“…Emergency clinical carts were more accessible, a higher proportion of patients were triaged appropriately, and drugs were more available. 12,17 QMMH had 882 staff as of December 2012, including 70 physicians and 284 registered nurses: this is 37% more than the 642 staff at QE II, with most of the additional staff in clinical and allied health positions. In light of these quantitative findings, documented in more detail in other publications, 12,17 analysis of qualitative data provides an opportunity to better understand how the model of the PPP had achieved these results.…”
Section: Background Of the Lesotho Pppmentioning
confidence: 99%
See 1 more Smart Citation
“…The government received more value for its money, patient fees remained the same, and quality improved. 24,25 Table A1).…”
Section: Modelmentioning
confidence: 99%
“…10 A 2014 Oxfam analysis found that the IFC's $1bn Health in Africa initiative, which channels capital to healthcare firms, had primarily targeted wealthy and middle class people-for example, by investing in costly urban hospitals. 11 Through its advisory work, the IFC also supported an agreement between the government of Lesotho and a private firm to build and operate a new hospital in the capital city; although the hospital achieved important service improvements, 12 it also consumed over half the annual health budget and squeezed out spending for more basic health services for rural poor citizens, while expecting to pay attractive returns to private investors. 13 Sridhar and colleagues concluded: "The World Bank Group more broadly is reinventing itself, from a lender for major development projects to a broker for private sector investment."…”
Section: Health Equity and Market Solutions?mentioning
confidence: 99%